Kemampuan penggunaan kara dan node pada mahasiswa semester V tahun 2020 prodi pendidikan bahasa jepang unp - retno putri; Damai Yani (Universitas Negeri Padang, 2023)
This research is motivated by the students' difficulties in understanding the use of kara and node which have the same meaning but have different meanings in Japanese sentences. The purpose of this study is to determine the ability to use kara and node to express cause and effect in a Japanese sentence. This type of research is quantitative research with descriptive methods. The population in this study was students in the fifth semester of the 2020 entry year Japanese Language Education Study Program, UNP. Thesample in this study were 30 students who were determined using a random sampling technique.The data in this study are the results of kara andnode tests. Based on the research results, it is known that the ability to use kara and nodes to express cause and effect in a Japanese sentence is generally known to have the qualification of 'sufficient' with an average score of 56.6. Theindicators are able to determine the correct use ofkara and nodesin Japanese sentences. With the highest value of kara and node in a sentence is 90, the lowest value is 30.